Association of Placenta Previa with Previously Scarred and Non Scarred Uterus: A Descriptive Cross-Sectional Study - Shah, Diwakar Kumar; Bhakta, Shalini; Yadav, Ashis; Thakur, Anita; Thakur, Nabraj (Nepal Journal of Health Sciences, 2024)
Introduction: Placenta previa, where the placenta is partially or completely placed in the lower uterine segment, is a major contributor to vaginal bleeding during pregnancy and affects 0.4-0.5% of all labors. Its exact cause is uncertain but is believed to be linked to aberrant endometrial vascularization caused by scarring or atrophy from prior trauma, surgery, or infection.Objective: The objective of this study was to establish an association between the placenta previa and the scarring of uterus.Methods: A cross-sectional study was conducted on pregnant women at Nobel Medical College Teaching Hospital, Biratnagar, from November 2021 to October, 2023. Ethical approval and written consent were obtained from all participants. Using convenient sampling technique, the study involved 57 participants out of 3576 patients who were admitted for Lower Segment Cesarian Section.Results: A study of 3576 patients admitted for Lower Segment Cesarian Section at Nobel Medical College Teaching Hospital, we found 57 cases of placenta previa over 24 months. The incidence was 1.59%, with 1.82% in patients with a previous history of LSCS and 1.51% without any history of scarring. The results showed no association between placenta previa and uterine scarring.Conclusion: The study found no association between the incidence of placenta previa and scarred/non-scarred uterus, but a slightly higher likelihood of having placenta previa in those with a history of uterine scarring.